Mammary duct ectasia with periductal mastitis presenting as a painful subareolar lump confirmed on triple assessment (Indian Journal of Case Reports, 2026)
Mammary duct ectasia with periductal mastitis is a benign, non-proliferative breast condition commonly affecting perimenopausal women between 40 and 50 years of age. It is characterized by dilatation of the subareolar ducts, accumulation of inspissated secretions, and subsequent periductal inflammation and fibrosis. We report the case of a 43-year-old female who presented with an acutely painful, ill-defined, mobile subareolar lump in the right breast of 4-day duration, without nipple discharge, fever, or axillary lymphadenopathy. She had a background of hypothyroidism and recent menstrual irregularity. Ultrasonography revealed bilateral ductal ectasia with inspissated secretions and periductal fat stranding in the right breast, which was classified as BIRADS III. Fine needle aspiration cytology demonstrated benign ductal epithelial and myoepithelial cells against a hemorrhagic, inflammatory background with numerous cyst macrophages and no cytological atypia, consistent with a benign lesion (Yokohama Category 2). Concordance of clinical, radiological, and cytological findings allowed a confident benign diagnosis of duct ectasia with periductal mastitis, avoiding unnecessary biopsy. This case underscores the importance of the triple assessment approach in evaluating breast lumps and highlights the potential of duct ectasia to mimic malignancy clinically.